Beckettian Pedagogies: Learning through Samuel Beckett. Issue 1 (April 2020) - Heron, Jonathan; Johnson, Nicholas
Abstract : This essay considers what it might mean to learn 'through' Beckett, inaugurating a critical pedagogy that could be called 'Beckettian'. By integrating existing strands of scholarship on Beckett and his relationship to education, the essay draws a distinction between the 'practical' and 'biographical' ways of thinking about Beckett and learning. This draws on previous work within the field, but also proposes a new vocabulary – derived from an interdisciplinary encounter with the scholarship of teaching and learning and the philosophy of education, especially 'critical pedagogy' – through which the possibility of 'Beckettian pedagogies' might be manifested. Recalling Beckett's biographers, his work's fundamental silence haunts most attempts to contain, explain, avoid or domesticate it. The essay proposes that a critical pedagogy of Beckett must be grounded in the concept of openness, especially in the notion that 'void' is a productive category, and in the embodiment of an evolving ecology of praxis . This alternative pathway reflects on the philosophy of education inherent within Beckett as an idea, engaging with 'Beckettian pedagogies' in an entangled sense of instruction, guidance and teaching with a particular focus on the latter in terms of the theory or principles of education. This move does not require abandoning existing traditions, but rather gathering them under new light, by placing the biographical Beckett (1906–89) in juxtaposition with the praxis of Beckett (ongoing) and the contemporaneous notion of critical pedagogy, as expounded by several scholars including Paulo Freire (1921–97). Beckettian pedagogies therefore remove dormant assumptions, habits of mind, and hierarchies that impede exploration to enable a move away from the curriculum, or toward a curriculum of unlearning and uncertainty, thereby disrupting the entrenched powers that Beckett saw fit to resist.